Partnership between a private university and a company: a study case (Research, Society and Development, 2016)
This paper aims to understand which are the real advantages that a private University gained (acquired) when established a partnership with an entreprise and vice versa , giving start to a project entitled Pre-Consultants UnP -Sebrae / RN. Through this study we sought to understand how this partnership was advantageous for both parties, besides analyzing motivators and trust factors in the partnership. The research method used was the case study. Two semi-structured interviews were applied to both organizations and submitted to a content analysis technique. The results shows that organizational learning, knowledge transfer and the desire to form more qualified professionals in the Entrepreneurship field were great advantages acquired for both sides.